THE IMPACT OF DEVELOPMENT POLICY ON SUPPLY AND DEMAND SOYBEAN IN INDONESIA - Rusdi, Mr (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
This research discusses of developing soybeans on supply and demand in Indonesia. To answer these objectives, the goal of econometrics is to use system model of equations with estimation using the 2SLS method. The results show that amount of national soybean demand is strongly influenced by soybean prices at the wholesalers, population and per capita income. The amount of soybean demand is very responsive to changes in population. While the number of bids is influenced by soybean production, imports, and supplies. Policy simulation results 10 percent increase in soybean prices at the farmer  will have an impact on increasing soybean production by around 9.58%. This increase caused by increasing in harvested area of ??7.71%. Eliminating urea subsidies by 60% will have an impact on declining soybean productivity by 42.79%, then decreasing agricultural land of oybean which is 38.62% and productivity of 5.02%.